Distribution of the clover root weevil biocontrol agent in the North Island of New Zealand - Gerard, P.J.; Eden, T.M.; Wilson, D.J.; Burch, G. (New Zealand Plant Protection, 2008)
The Irish wasp Microctonus aethiopoides was released in 2006 as a biocontrol agent for the clover root weevil Sitona lepidus a serious pest of white clover in New Zealand Following successful establishment two strategies were implemented to accelerate the widespread establishment of the parasitoid throughout the North Island The first approach was the establishment of regional nursery sites that act as point sources for natural and assisted dispersal With the assistance of Regional Councils and major landowners these were set up at sites favourable to the wasp and local people were provided the training and support to undertake collections and distribution of parasitized weevils Secondly samples of parasitized weevils were distributed for release directly to farmers through pastoral industry networks and events Initial results indicate that while the parasitoid established rapidly at Taranaki and Waikato nursery sites as anticipated it has failed to establish in Northland in two successive seasons